WORKERS AS PETITIONERS: DISCURSIVE PRACTICES OF IRANIAN TEXTILE WORKERS, 1906-1941 - AFACAN, SERHAN (My University, 2020)
This study deals with the discursive practices of Iranian workers and their relationship with the state from the Constitutional Revolution in 1906 until the end of Reza Shah’s reign in 1941 with a particular focus on the late 1920s and 1930s. Although organized labour, such as trade unions, as well as collective labour actions, such as strikes, are undeniably important in examining the trajectory of Iranian workers’ relationship with the state, only a small segment of workers joined in them, compared to their overall number. Thus, this article provides an analysis of workers’ petitions as a more common and non-confrontational form of labour activism, and an often-deferential means of negotiating with the state over working and living conditions. In the main, it argues that the discursive formation of the Iranian working class, in its broadest sense, preceded its material formation. Also, since non-striking workers were not necessarily passive recipients of state policies, an emphasis is made on workers’ petitions, mostly from the textile industry, to show how they tried to work the system ‘to their minimum disadvantage’, to use Eric Hobsbawm’s phrase.

Bu çalışma 1920 ve 1930’lara özel olarak eğilmek kaydıyla, 1906 Anayasal Devrimi’nden Rıza Şah döneminin sonuna tekabül eden 1941 yılına kadar olan sürede İran işçilerinin söylemsel pratiklerini ve devletle olan ilişkilerini analiz etmektedir. Her kadar sendikalar ve diğer işçi örgütleri gibi organize oluşumlar yahut grevler gibi kolektif işçi eylemleri İranlı işçilerin devletle olan ilişkilerini incelemek açısından önemli olsa da toplam sayılarına nazaran, en azından incelenen dönemde, işçilerin ancak küçük bir bölümü bu tarz oluşum ve eylemlerde yer almıştır. Bu nedenle eldeki makale, daha yaygın ve çatışmacı olmayan bir emek aktivizmi türü ve aynı zamanda çoğunlukla riayetkâr bir üslupla devletle çalışma ve yaşam koşullarının pazarlığını yapma kanalı olarak işçilerin dilekçelerini ele almaktadır. Temel olarak makalede, her şeyden önce en geniş anlamıyla işçi sınıfının söylemsel oluşumunun maddi oluşumuna takaddüm ettiği öne sürülmektedir. Ayrıca, işçilerin grev yapmıyor oluşu illaki devlet politikaları karşısında pasif alıcı konumunda bulundukları anlamına gelmediği için, Eric Hobsbawm’ın ifadesiyle işçilerin sistemi nasıl “asgari zararlarına” getirmeye çalıştıklarını göstermek için çoğu tekstil işçilerine ait olmak üzere işçi dilekçeleri tetkik edilmiştir.
Dilekçeciler Olarak İşçiler: İranlı İşçilerin Söylemler Pratikleri, 1906-1941